Recent trends in self-reported utilization of colonoscopy and fecal occult blood test in Europe: analysis of the European Health Interview Surveys 2013-2015 and 2018-2020 - Ola, Idris; Cardoso, Rafael; Hoffmeister, Michael; Brenner, Hermann (European journal of epidemiology, 2025)
Despite increasing implementation of colorectal cancer (CRC) screening programs in Europe, utilization of screening tests has varied significantly over the years. We examined recent trends in the utilization of colonoscopy and fecal occult blood test (FOBT), the primary tests recommended for CRC screening, across European countries with various screening programs. Population-based data from the second and third waves of the European Health Interview Survey (EHIS) were analyzed to determine changes in utilization of fecal occult blood test within the preceding 2 years or colonoscopy within the preceding 10 years among people aged 50-74 years between 2013-2015 and 2018-2020. Absolute percentage changes (APC) in screening test use were calculated in each country and subgroup meta-analyses were conducted using random effects models to estimate the pooled APCs and their 95% confidence intervals across different categories of screening offers. A total of 234,251 respondents across 28 European countries were included in the analysis. The increase in use of either test was highest among countries which fully rolled out nationwide organized screening programs with fecal tests between 2013-2015 and 2018-2020 (increases ranging from 19.1% units in Belgium to 46.3% units in The Netherlands) and was lowest among countries with opportunistic offering of fecal test, colonoscopy or flexible sigmoidoscopy (from − 3% units in Germany to + 12.2% units in Slovakia). Changes in screening programs were strongly associated with higher rates of utilization of colonoscopy and fecal occult blood test across all screening offers. Our findings highlight that well-organized and dynamic population screening strategies can rapidly and sustainably increase utilization of CRC screening tests in Europe.